The Concept of Actio Pauliana Creditor Law Bankruptcy Boedel Dispute Process to Achieve Substantive Justice - Marpi, Yapiter; Purwadi, Hari; Suwadi, Pujiyono (Magister of Law, Faculty of Law, University of Mataram, 2023)
This Actio pauliana is actually a lawsuit that substantively attempts to confirm that the debtor's legal actions are declared legally invalid if they harm the creditor. In bankruptcy law, actio pauliana is an important instrument so that substantive justice, especially for creditors, can be implemented optimally. This research aims to analyze the substantive justice aspects of actio pauliana in the field of bankruptcy law. This research is normative legal research by prioritizing conceptual and statutory approaches. The research results confirm that the essence of actio pauliana in bankruptcy disputes is viewed from the aspect of substantive justice, namely that it is aimed at protecting creditor rights, especially when there are debtor legal actions that can harm creditors. Apart from that, Actio Pauliana also emphasizes the restitutive aspect as per the substantive justice concept, namely being able to declare the debtor's actions to have no legal force if the action is detrimental to the debtor and reduces the number of bankruptcy debts as has been determined. In its development, the actio pauliana lawsuit in bankruptcy actually represents the fairness aspect as a manifestation of substantive justice so that in the future the actio pauliana lawsuit will not only represent factual losses, but also include potential losses that directly harm creditors and can be proven fairly and properly